DAKWAH INKLUSIF: ALTERNATIF PENGUATAN MODERASI BERAGAMA - Nahna Nailussa’adah (Nusantara Hasana Journal, 2022)
Indonesia is a pluralistic country, meaning that its people are plural or diverse in terms of race, ethnicity, language, culture and religion. Of course, conflict in the community cannot be avoided, so religious moderation is a discourse as well as Indonesia’s commitment to maintain national unity and integrity. In this regard, religious moderation needs to strengthen its foundation with other discourse alternatives. The alternative discourse is inclusive da’wah or can instill religious values ​​that are inclusive. In fact, the main goal of all of them is the noble values ​​of humanity, the value of tolerance, and anti-violence to maintain diversity. This research is based on library research with clear analytical content regarding religious moderation and inclusive da’wah.